HPLC Method for Estimation of Lercanidipine in Pharmaceutical Dosage Froms - N.V. GOPAL, PASUMARTHY; HEMAKUMAR, A.V.; PADMA, S.V.N. (Asian Journal of Chemistry, 2010)
A reverse phase HPLC method has been developed for the determination of lercanidipine for the estimation of the lercanidipine in its tablet dosage forms using RP-C18 column. The mobile phase (methanol, phosphate buffer pH 8) was pumped at a flow rate of 1 mL/min in the ratio of 90:10 and the eluents were monitored at 290 nm. The intra- and interday variation was found to be less than 2 % showing high precision of the assay method. The mean recovery of the drug from the solution containing 20 or 30 μg/mL was 98.7 ± 1.20 % indicating high accuracy of the proposed HPLC method. Due to its simplicity, rapidness, high precision and accuracy, the proposed HPLC method may be used for determining lercanidipine in bulk drug samples or in pharmaceutical dosage forms.